A Flexible and Transparent Thin Film Heater Based on a Silver Nanowire/Heat‐resistant Polymer Composite. Issue 11 (14th August 2014) - Li, Junpeng; Liang, Jiajie; Jian, Xiang; Hu, Wei; Li, Juan; Pei, Qibing
<x xml:space="preserve">Abstract</x> It has been a challenge to develop a new transparent conductor to replace the brittle and expensive indium tin oxide (ITO) film to make film heater with high transmittance in the visible wavelength range, high surface conductivity and mechanical flexibility. Here, we report the synthesis of a transparent composite film comprising a silver nanowire (AgNW) percolation network inlaid in the surface of a heat‐resistant polymer film. This composite conductor has a figure‐of‐merit sheet resistance of 25 Ω · sq−1 with 86.4% transmittance at 550 nm. The composite film possesses outstanding heat‐resistant property and can generate high temperature up to 230 °C at low operation voltages as an efficient thin film heater. Compared with the film heaters previously reported, the composite film heater shows faster heating response and higher saturation temperature under the same input voltage. The film heater could be bent to 10 mm diameter and the generated temperature decreased by less than 3 °C after 3 000 bending cycles.<inline-graphic xlink:href="ark:/27927/pgh2ck9dssm" content-type="mame201400097-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />